A traction force threshold signifies metastatic phenotypic change in multicellular epithelia. Issue 36 (2nd September 2019) - Zhang, Yao; Shi, Xuechen; Zhao, Tiankai; Huang, Changjin; Wei, Qiong; Tang, Xin; Santy, Lorraine C.; Saif, M. Taher A.; Zhang, Sulin
Abstract : Using extracellular matrix control of cellular mechanics, we establish that cellular force threshold can also mark in vitro metastatic phenotypic change and malignant transformation in HCT-8 cell colonies. Abstract : Cancer metastasis has been believed as a genetically programmed process that is commonly marked by biochemical signals. Here using extracellular matrix control of cellular mechanics, we establish that cellular force threshold can also mark in vitro metastatic phenotypic change and malignant transformation in HCT-8 cell colonies. We observe that for prolonged culture time the HCT-8 cell colonies disperse into individual malignant cells, and the metastatic-like dispersion depends on both cell-seeding gel stiffness and colony size. Cellular force microscopies show that gel stiffness and colony size are also two key parameters that modulate cellular forces, suggesting the correlations between the cellular forces and the metastatic phenotypic change. Using our recently developed biophysical model, we construct an extracellular traction phase diagram in the stiffness-size space, filled with experimental data on the colony behavior. From the phase diagram we identify a phase boundary as a traction force threshold above which the metastatic phenotypic transition occurs and below which the cell colonies remain cohesive. Our finding suggests that the traction threshold can be regarded as an effective mechano-marker for the onset of the metastatic-like dispersion and malignant transformation.